2021
DOI: 10.1371/journal.pone.0259702
|View full text |Cite
|
Sign up to set email alerts
|

Unraveling the probiotic efficiency of bacterium Pediococcus pentosaceus OBK05 isolated from buttermilk: An in vitro study for cholesterol assimilation potential and antibiotic resistance status

Abstract: The present study describes the probiotic potential and functional properties of the lactic acid bacterium Pediococcus pentosaceus OBK05 isolated from buttermilk. The isolate OBK05 was assessed for its probiotic properties. The isolate showed notable tolerance to pH 2.0 and 3.0 (8.44, 8.35 log CFU/mL), oxbile of 0.5% at 2 and 4 h of incubation (6.97, 6.35 log CFU/mL) and higher aggregation (auto-aggregation, adhesion to hydrocarbons) than the referral strain, Lactobacillus acidophilus MTCC 10307. The adhesion … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 10 publications
(4 citation statements)
references
References 49 publications
1
3
0
Order By: Relevance
“…The cholesterol-lowering effect of probiotic bacteria is primarily based on BSH activity [ 41 ]. Our findings are similar to previous studies [ 42 ] who reported bile salt precipitation around the colonies of LAB. The growth of three LAB isolates was observed at temperatures ranging from 20–50°C and able to tolerate 4–9.5% NaCl concentrations while L .…”
Section: Discussionsupporting
confidence: 93%
“…The cholesterol-lowering effect of probiotic bacteria is primarily based on BSH activity [ 41 ]. Our findings are similar to previous studies [ 42 ] who reported bile salt precipitation around the colonies of LAB. The growth of three LAB isolates was observed at temperatures ranging from 20–50°C and able to tolerate 4–9.5% NaCl concentrations while L .…”
Section: Discussionsupporting
confidence: 93%
“…2,2-diphenylpicrylhydrazyl (DPPH; Himedia, Mumbai, India) assay was used to determine the antioxidant activity of bacterial cell-free supernatant (CFS) as described by Bhukya and Bhukya (2021). The reference standard was ascorbic acid (1 mg/ml).…”
Section: Antioxidant Assay By Dpph Methodsmentioning
confidence: 99%
“…Horizontal transfer of trimethoprim resistance from the P. pentosaceus strain OBK05 to four different Gram-positive pathogens was also shown by mating assays within a cheese matrix and was hypothesized to be mediated by a plasmid. However, the corresponding resistance gene was not identified but was only supposed to be plasmid-encoded since plasmid curing impaired the acquisition of the resistant phenotype by the recipient strains [ 29 ]. Noteworthy, conflicting results concerning transferability were obtained for some of the tet and erm genes: for example, the erm B, tet M and tet S genes were successfully transferred from L. delbrueckii ssp.…”
Section: Amr Detection Within the Foodborne Bacterial Reservoirmentioning
confidence: 99%
“…Indeed, phenotypic AMR as the only confirmation method is often unreliable, and, as suggested by other authors, the combination of molecular analysis with phenotypic tests is recommended [ 71 ]. Among the molecular approaches, detection of AMR genes by means of PCR or Southern hybridization proves the effective transfer of such genes to the recipient strains, and these methods were adopted in most articles reported in Table 2 , while two of them applied only phenotypic tests [ 29 ] or no confirmation [ 35 ]. Moreover, in addition to the molecular detection of the transferred AMR genes, the genotyping of the transconjugants provides complete proof of a successful HGT event.…”
Section: Amr Detection Within the Foodborne Bacterial Reservoirmentioning
confidence: 99%